A study of stochastic processes of asset pricing - Lim, Ngee Woon (2014)
Wherever there are valuable assets to be traded, there are incentives to develop markets to organise that trade more efficiently. In modern societies the securities markets are usually among the best organised and virtually always the largest in terms of value of sales. The largest in terms of value of sales. The prices of such securities are typically very sensitive, responsive to all events, that cast light into the hazy future.